2008
DOI: 10.1016/j.jvs.2007.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent secondary patency rates of upper extremity Vectra Vascular Access Grafts and transposed brachial-basilic fistulas with aggressive access surveillance and endovascular treatment

Abstract: Aggressive graft surveillance and endovascular treatment methods can yield equivalent long-term secondary patency rates between Vectra graft and TBB fistulas. The advantage of earlier use of Vectra graft must be balanced against the need for more frequent secondary interventions and the risk of graft infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 28 publications
2
61
0
Order By: Relevance
“…Several studies have compared various BBAVF with AVG. 3,[11][12][13][14][15][16][17][18][19] In particular, if the patient is already undergoing dialysis via a central venous permacath, one must weigh the risks of prolonged central vein catheterization while awaiting BBAVF maturation with the increased complication rate associated with AVG placement. A previous study showed an increased rate of thrombosis with AV graft compared with BBAVF (relative risk, 2.6; 95% CI, 1.3-5.3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have compared various BBAVF with AVG. 3,[11][12][13][14][15][16][17][18][19] In particular, if the patient is already undergoing dialysis via a central venous permacath, one must weigh the risks of prolonged central vein catheterization while awaiting BBAVF maturation with the increased complication rate associated with AVG placement. A previous study showed an increased rate of thrombosis with AV graft compared with BBAVF (relative risk, 2.6; 95% CI, 1.3-5.3).…”
Section: Discussionmentioning
confidence: 99%
“…2,16 AVG and BBAVF were again compared in 2008, showing increased early complications with BBAVF and increased late thrombosis with AVG. 17 Several other technical issues remain unresolved with respect to BBAVF creation. One issue is the optimal timing of superficialization for the two-stage procedure.…”
Section: Discussionmentioning
confidence: 99%
“…11,16,36,37 In a recent study, equivalent secondary patency of BVT and brachial artery-axillary vein polyetherurethaneurea (Vectra, Bard Inc, Tempe, Arizona, USA) grafts were reported. 38 However, to achieve this, significantly more thrombectomy and angioplasty procedures were performed in failing grafts compared with BVT fistulas. With respect to complications, there were significantly more infections requiring removal of the access in the AVG group.…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies would, however, need to be further evaluated given the high re-intervention rate required to maintain long-term patency of arteriovenous grafts. 27,28 This study highlights the burden of access related complications and morbidity associated with BBF. The overwhelming majority of patients required an inpatient hospital stay with mean length of hospital admission for BBF creation 2 days compared to 0.5 days for BCF creation.…”
Section: Utilization Of Avfmentioning
confidence: 92%